NEWS AND FAKE NEWS: a reflexion about two aspects of the phenomenon of mutation, applied to contemporary journalism - JORGE, Thaïs de Mendonça (2018)
This article brings the concept of mutation from the biological sciences to journalism and tries to show how the methods of nature can be seen within the field of news. The news would thus be an organism that can be observed in the environment itself and in the conviviality with its correlates, being able to be classified in types or categories according to the characteristics it presents. In this case, the so-called fake news can be framed as a phenomenon of mutation focusing on the news, although it is not news in its strict sense, but is disguised as such to deceive the public. The term mutation in journalism serves not only to understand the changes in the news, but also to analyze the social and media environment. This involves, in the context of newsmaking, the way in which the products are elaborated and the culture that underlies the organization of journalists and traditional journalistic companies, within a context of late postmodernity, where institutions are questioned, the hierarchy of presentation of the data is discussed and the user's own search for information is based on independence and personalization criteria.NEWS AND FAKE NEWS: a reflexion about two aspects of the phenomenon of mutation, applied to contemporary journalism